Vibration Impact on Potentially Liquefactions Slope Deformation - Yusuf, Rakhmat; Haryadhi, Yayan; Dermawan, Herwan (Fakultas Teknik UB, 2021)
In an area that has potential for earthquake has possibility of losing soil stability and causing physical soil damage, one of them is liquefaction. This research was conducted to determine the magnitude of deformation on slopes with potentially liquefaction. The soil slope samples were tested using shaking table with slope 6°, 12°, 18°, 24° and the frequency was set 6.6 Hz, 7.4 Hz, 8 Hz, 9.5 Hz. Research began with examination of soil physical properties which had unit weight of density 1.81 gr/cm3, moisture content 2.31%, specific gravity 2.72, sand with coefficient of uniform is 2.1, coefficient curvature is 0.98 and angle of repose is 23.962°. By giving earthquake acceleration of 0.4g, 0.5g, 0.6g and 0.7g in the soil slope sample that was tested by shaking table, it was liquefaction occurred. Results of research, the greater slope and frequency given, so the lateral and axial deformation will increase. Minimum lateral deformation occurs at frequency 6.6 Hz with a slope 6° and maximum lateral deformation is 17 cm at frequency 9.5 Hz with a slope 24°, while minimum axial deformation is 0.5 cm at frequency 8 Hz with a slope 6° and a maximum axial deformation is 5 cm at frequency 9.5 Hz with a slope 24°, but 12-degree slope can considered as a safe slope for slope which holding vibration.